Magnetic Properties of Elliptical and Stadium-Shaped Nanoparticles: Effect of the Shape Anisotropy - Altbir-Drullinsky, D; Escrig-Murua, J; Corona-Gonzalez, R (2012)
Elliptical and stadium-shaped nanoparticles as a function of their geometry have been investigated using numerical simulations. The effect of the shape anisotropy of the particles on coercivity and remanence together with the angular dependence of the remanence and coercivity are addressed. Our results demonstrate that the stadium-shaped particles have many of the outstanding properties of elliptical particles, but also have unique properties, such that the coercivity and remanence remain stable for a wide range of geometry parameters, and exhibit a peculiar angular dependence in the coercivity. These properties suggest that they can be useful for applications in the area of magnetic recording systems. © 2012 Elsevier B.V.